2013
DOI: 10.1002/app.39117
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and use of magnetic poly(glycidyl methacrylate) resin in drinking water treatment

Abstract: Magnetic poly(glycidyl methacrylate) (m-PGMA) was synthesized and characterized, and its efficiency in removing natural organic matter (NOM) and carbamazepine (CBZ) from synthetic water was studied. The effects of factors such as time and m-PGMA dosage on NOM removal were investigated. Furthermore, magnetic ion exchange resin (MIEX V R ) was used for comparison with m-PGMA in CBZ removal. m-PGMA was found to have a strong magnetic character whose specific saturation magnetization and mass fraction of magnetite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…In addition, the CH stretching in the methyl and methylene group in the PGMA composites was observed at 2940 cm −1 . Furthermore, a broad absorption band associated with OH stretching vibrations of hydroxyl group was also found at around 3390 cm −1 . These results demonstrated that the PGMA composites had been successfully synthesized.…”
Section: Resultsmentioning
confidence: 66%
“…In addition, the CH stretching in the methyl and methylene group in the PGMA composites was observed at 2940 cm −1 . Furthermore, a broad absorption band associated with OH stretching vibrations of hydroxyl group was also found at around 3390 cm −1 . These results demonstrated that the PGMA composites had been successfully synthesized.…”
Section: Resultsmentioning
confidence: 66%
“…However, at near neutral pH of synthetic wastewater employed in this study the adsorption of CBZ is somewhat less favorable on negative silica surface [15]. The MAA coated NPs exhibited somewhat better adsorption toward CBZ than in control column, possibly from a higher specific surface area, and larger pore volume of MAA functionalized NPs [16].…”
Section: Cbz and Dtz Removalmentioning
confidence: 71%
“…A different magnetic anion exchange resin (NDM-1) was synthesized in which the functional group was triethylamine instead of trimethylamine on MIEX resin and as a result, the NDM-1 resin showed greater adsorption of nitrate than MIEX resin in the presence of sulfate [86], similar to the results discussed for perchlorate. Another magnetic resin, magnetic poly(glycidyl methacrylate), was synthesized and compared with MIEX resin for removal of DOM and carbamazepine [87].…”
Section: Comparison With Other Anion Exchange Resinsmentioning
confidence: 99%